Use of natamycin and ketoconazole suppositories in the treatment of recurrent vulvovaginal candidiasis - I.I. Ivanova; Yu.E. Dobrokhotova (LCC «Medicine-Inform», 2018)
Use of natamycin and ketoconazole suppositories in the treatment  of recurrent vulvovaginal candidiasis I.I. Ivanova1, Yu.E. Dobrokhotova2 1 Pirogov Russian National Research Medical University, Moscow, Russian Federation 2 Clinical Diagnostic Center «Medsi» on Krasnaya Presnya, Moscow, Russian Federation According to statistics, 50% of women had vulvovaginal candidiasis at least two times in their lives, and 5% experienced relapses every two months. A peak incidence is noted at the age of 20-45 years. A causative agent of candidal colpitis and vulvitis (vulvovaginitis) are yeast-like fungi of the Candida genus, belonging to opportunistic pathogenic microorganisms. The reasons for the high prevalence of vulvovaginal candidiasis are quite numerous: any diseases of the macroorganism occurring with a weakening of immune system or impairment of the secretory component of the immune system (hypo- and hyperthyroidism, diabetes mellitus, dishormonal conditions, immunodeficiency itself) create conditions for excessive reproduction and fungal adhesion. The diagnosis of vaginal candidiasis is confirmed by the Candida yeast cells culture isolation from the vulva and vagina. Despite the proven efficacy of recommended antifungal agents and relatively slow development of resistance in fungi, an epidemiological situation of candidiasis in the world is not improving. Natamycin is highly effective in treating patients with recurrent vulvovaginal candidiasis. Patients noted the convenience of drug application (no leakage effect) and the relief of symptoms already on the second day of therapy without disrupting their habitual lifestyle, which contributes to compliance. KETOCONAZOLE by "Avexima" is more suitable for women with chronic recurrent vulvovaginal candidiasis in the period of perimenopause and postmenopause due to a wide spectrum of action. Thus, PRIMAFUNGIN® and KETOCONAZOLE by "Avexima" have a positive therapeutic efficacy when used only once a day without unpleasant side effects in the form of patient subjective assessment, which increases the compliance of the therapy and does not violate the quality  of life of patients. Key words: vulvitis, colpitis, vulvovaginal candidiasis, Candida, compliance, natamycin, Primafungin, Ketoconazole. For citation: Ivanova I.I., Dobrokhotova Yu.E. Use of natamycin and ketoconazole suppositories in the treatment of recurrent vulvovaginal candidiasis. Russian Journal of Woman and Child Health. 2018;1(2):179-183.